Open hermeneutics: André Scrima’s «éclatement de la parole "en moi"» (I) - Dumbravă, Daniela (Diakrisis, 2022)
Towards the end of the 1960s, in the well‑known Enrico Castelli (1900‑1977) colloquia, while intensively discussing the topic of demythologization, scholars concluded that theological language is fundamental in exploring it. Thus, the topic of the analysis of theological language: the Name of God, became prevalent for them and they began to think that a distinction between the terms religious and theological would be desirable, avoiding scandalous formulas for the field of theology. According to Karl Jasper, God is just a chest of something indicible. André Scrima presents himself in the debate with an original proposal, namely to think of theological language, in the broadest sense of this concept, as enclosing religious discourse. In the beginning, speaking theologically should happen in the Name of God, Scrima asserts; at Jasper’s antipodes, he places the Name of God as the origin and mystery that generates speaking theologically. This article aims first of all to bring the question of theological language back into the academic space that is more interested in the phenomenological issues promoted in Enrico Castelli’s thought laboratory in Rome.